Wise Use of Social Media in the Digital Era at SMP Negeri 7 Gorontalo - Moh. Imron Rosidi; Ismaul Fitroh; Renol Hasan; Sutrisno Mohamad; Resmiyati Yunus (Jurnal Kabar Masyarakat, 2026)
This community service activity aims to improve the understanding and awareness of students at SMP Negeri 7 Gorontalo regarding the wise use of social media by strengthening their digital literacy, communication ethics, digital security, personal data protection, and ability to verify information. The program was implemented using a participatory approach, beginning with needs assessment, the development of educational materials, interactive workshops, group discussions, case studies, Q&A sessions, and group reflection. Evaluation was conducted qualitatively through observation of student participation, documentation of activities, and feedback gathered throughout the educational process. The results of the activity showed an increase in participants’ awareness of the importance of digital communication ethics, their ability to recognize the risks of spreading unverified information, their understanding of personal data protection, and their commitment to using social media responsibly in their daily lives. Reflections on the activity also revealed that active participant engagement and school support play a crucial role in building a positive and sustainable digital culture. This program provides a participatory digital literacy education model that can be replicated in other educational institutions as a strategy for strengthening students’ digital character in the era of digital transformation.